Makran - das rückständigste Gebiet Irans - Pozdena, Hans (ERDKUNDE, 1975)
In terms of natural resources, Makran is barren and extremely inhospitable. Agriculture is only possible with artificial irrigation. Most of the area can only be used for extensive pastoral activity. There is a clear social differentiation between the nomadic shepherds of the Makran mountains and the farmers of the oases. Up to the reign of Reza Shah, the area was divided for all practical purposes into independent tribal dukedoms. These no longer exist but the traditional divisions of the Baluch people are still relevant, except that Persians have now taken over the top positions in the social hierarchy. If the area was once characterised by a subsistence economy, today many men go as migrant workers to Karachi and the oil sheikdoms. Because of the paucity of communications links, Makran has not yet been integrated into the Iranian state. It is economically dependent on Arabia and Pakistan. Most Baluchs do not feel themselves to be Iranian citizens. Only the new schools and radio service can be expected to generate an Iranian national feeling in the Baluch minority.